Reducing Smoking Among People With Schizophrenia: Perspectives on Priorities for Advancing Research - Baker, Amanda L.; Robson, Debbie; Lawn, Sharon; Steinberg, Marc L.; Bucci, Sandra; McNeill, Ann; Castle, David J.; Bonevski, Billie (Frontiers in Psychiatry, 2018)
Although tobacco smoking is very common among people with schizophrenia and has devastating effects on health, strategies to ameliorate the risk are lacking. Some studies have reported promising results yet quit rates are much lower than in the general population. There is a need to advance research into smoking cessation efforts among people with schizophrenia. We posed the following question to five leading international experts in the field: “What are the top three research ideas we need to prioritize in order to advance the field of reducing smoking amongst people with schizophrenia?” They identified three broad priorities: (i) deeper understanding about the relationship between smoking, smoking cessation and symptomatology; (ii) targeted, adaptive and responsive behavioural interventions evaluated with smarter methodologies; and (iii) improvements in delivery of interventions. Efforts should be made to establish a collaborative international research agenda.